One-pot sequential kinetic profiling of a highly reactive manganese catalyst for ketone hydroboration: leveraging σ-bond metathesis via alkoxide exchange steps = One-pot sequential kinetic profiling of a highly reactive manganese catalyst for ketone hydroboration : leveraging sigma-bond metathesis via alkoxide exchange steps - Vasilenko, Vladislav; Blasius, Clemens K.; Gade, Lutz H. (Journal of the American Chemical Society, 2018)
A comprehensive experimental and computational mechanistic study of the highly enantioselective hydroboration of ketones catalyzed by a manganese(II) alkyl boxmi pincer complex is reported. The catalyst operates at low catalyst loadings (down to 0.01 mol %) under very mild conditions (typically −40 °C) and facilitates the reduction of both aryl alkyl and dialkyl ketones with excellent selectivity (up to >95%ee). Catalyst activation pathways were investigated, demonstrating that a manganese(II) hydride and a manganese(II) alkoxide species are part of the catalytic cycle and can be generated via σ-bond metathesis of the alkyl precursor with the borane or by alcoholysis. Extensive kinetic experiments based on a “one-pot sequential kinetic profiling” approach under various conditions in combination with kinetic simulations reveal that two catalytic cycles are effective with this earth-abundant base metal catalyst: (i) a minor MnH/borane-mediated insertion cycle, in which the subsequent, product-releasing metathesis step is rate determining (km = 0.076 s-1), giving a background reaction, which is zeroth order in substrate concentrations, and (ii) a major MnOR/borane-based alkoxide exchange process, leveraging the high-barrier metathesis via the affiliation to an insertion step. The latter features non-integer reaction orders in both reagents due to a combination of an adduct formation step (ka = 2.12 M-1 s-1, k-a = 0.49 s-1) and a substrate insertion step of comparable rates (kai = 3.74 M-1 s-1). The kinetic findings are underpinned by high-level density functional theory calculations of the mechanism, control experiments, and kinetic isotope effect/Hammett/Eyring analysis in different concentration regimes. The study highlights the role of a rigorous mechanistic understanding of homogeneous catalytic processes in 3d metals for rational catalyst discovery and optimization.